Hubungan Pengetahuan Dengan Perilaku Masyarakat Tentang Penggunaan Antibiotik Di Desa Badan Kabupaten Sukoharjo - Noviana Fatmawati; Sri Saptuti Wahyuningsih (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2023)
The majority of people still use antibiotics inappropriately. If such incidents continue, they will lead to a condition called immunity to antibiotics. This study aims to obtain information about the relationship between knowledge, and the behavior of using antibiotics in the Badan, Sukoharjo Regency. This type of research is conservational research with a cross-sectional approach. This study used a measuring instrument in the form of a questionnaire, namely the knowledge and behavior questionnaire. Research data were analyzed using Pearson Product Moment. Respondents used in this study were 78 people. The results obtained were people is female (57.7%), aged 17-26 years (41%). The last education of the majority of respondents was high school (60.3%), the majority of respondents' jobs were private (51.3%). Respondents' knowledge with good knowledge category was 29.5%, sufficient category was 53.5%, less category was 14.1%, and bad category was 2.6%. The good behavior category is 41%, the sufficient is 55.1%, and the less is 3.8%. Pearson Product Moment calculation produces a significant value of 0.000. Correlation coefficient value of 0.512. The results of this study indicate that there is a significant correlation between knowledge and the behavior of using antibiotics in Badan Village, Sukoharjo Regency.